Salí de paseo - Williams, Sue, 1948-; Vivas, Julie, 1947- (San Diego : Harcourt Brace, 1995)
During the course of a walk, a young boy identifies animals of different colors.
"Libros viajeros."
Translation of: I went walking.
Book Links (A.L.A.)
Notable/Best Books (A.L.A.)
School Library Journal
K-3.
Keywords: Animals -- Fiction; Color -- Fiction; Spanish language materials; Stories in rhyme; Walking -- Fiction; Animals -- Fiction; Color -- Fiction; Spanish language; Stories in rhyme; Walking -- Fiction